Pertanggungjawaban Pidana Bagi Anggota TNI Yang Menjual Amunisi Ke KKB Papua Terhadap Disparitas Putusan Pengadilan Yang Berbeda - Wijoyo, R Ach Agus Purno; Hehanussa, Deassy Jacomina Anthoneta; Supusepa, Reimon (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The misuse of ammunition by Indonesian National Army personnel by selling to Separatist Armed Criminal Groups in Papua is an important concern for Indonesian National Army leaders and emphasis from the upper command if there are Indonesian National Army personnel who misuse firearms and ammunition to be processed in accordance with applicable law.Purposes of the Research: Analyse and formulate the criminal liability for Indonesian National Army members who sold ammunition to Papuan KKB separatists against the disparity of different court decisions.Methods of the Research: Normative legal research. The research approach is a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials through literature studies and then analysed through perspectives using qualitative methods.Results of the Research: Criminal liability for a defendant, especially in the case of misuse by selling ammunition to the Separatist Armed Criminal Groups in Papua against different verdicts (disparity of verdicts) must be seen from a legal point of view and standards applicable in the military, in the context of the Indonesian National Army selling ammunition to the Separatist Armed Criminal Groups or to Separatist Armed Criminal Groups sympathisers must get a fair legal process and the decision is based on the evidence presented in accordance with the legal facts. Although the legal process in court must run fairly and objectively, it is possible that court decisions can be different in the same case and the same article.